Regarding About the Cultural Attribution of Hill Forts in Braslav Poozerye (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: Dnieper-Dvina Culture; Early Hatched Ware Culture; Late Hatched Ware Culture; Hill fort Tarilovo; Hill fort Zazony; Hill fort Ratjunki; Settlement Pod